2021
DOI: 10.1093/workar/waab018
|View full text |Cite
|
Sign up to set email alerts
|

An Interpretative Phenomenological Analysis of Social Identity Transition in Academic Retirement

Abstract: One of the most serious challenges inherent in retirement transition is coping with social identity changes. We investigated social identity processes and the role of social engagement during retirement transition by examining the life narratives of recently retired university faculty (14 males and 5 females) from 12 different academic areas. The interviews were analyzed using interpretative phenomenological analysis (IPA). The results revealed one overarching theme—the centrality and importance of academic id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Skarupski et al (2020b), for example, reported that half of the academic medicine faculty aged 55 and older would consider part‐time employment and 39% would enjoy teaching following retirement. Models, whereby retirees continue to function in supportive academic roles, may have merit and may help to support retirees themselves, especially as social identity change is a major challenge for academic retirees (Miron et al, 2022). Part‐time employment is a viable means for institutions to support retirees' well‐being by promoting a gradual identity change.…”
Section: Discussionmentioning
confidence: 99%
“…Skarupski et al (2020b), for example, reported that half of the academic medicine faculty aged 55 and older would consider part‐time employment and 39% would enjoy teaching following retirement. Models, whereby retirees continue to function in supportive academic roles, may have merit and may help to support retirees themselves, especially as social identity change is a major challenge for academic retirees (Miron et al, 2022). Part‐time employment is a viable means for institutions to support retirees' well‐being by promoting a gradual identity change.…”
Section: Discussionmentioning
confidence: 99%
“…As such, employee should consider activities which would maintain the daily routine and keep one physically fit and maintain the professional identity. To achieve this aspect, literature indicates that most academics continue to work even after retirement to keep links with academia (Miron et al, 2022;Cahill et al, 2021Cahill et al, , 2022 while others engage in leisure activities and new hobbies (Agnew et al, 2013). Wang et al (2009) argued that retirement brings new concerns regarding how one would spend one's time, for example, by participating in leisure activities or other productive activities such as volunteer or paid work aimed to enhance post-retirement life satisfaction.…”
Section: 12mentioning
confidence: 99%
“…A thorough review of related literature produced only a handful of studies that explored academics' perspectives on retirement planning, particularly on activities which are involved when planning and perceptions of the right time for employees to start planning for their retirement life. Previous studies on retirement planning focused on the impact of financial knowledge (Mndzebele and Kwenda, 2020), transition experiences of retired academics (Cahill et al, 2022;Miron et al, 2022;Rowson and Phillipson, 2020), and retirement pension policy reforms (Mwakisisile and Larsson, 2021). In Tanzania, few studies have been conducted on retirement planning focusing on terminal benefit payment practices and their challenges (Haule, 2013), retirement planning mistakes (Amani and Fussy, 2022), challenges that can obstruct provision of retirement education (Mayemba, 2015), impact of retirement benefit on socio-economic development (Nyangarika and Bundala, 2020), and age-based perceptions on retirement income spending plans and actual spending upon retirement among employees in Higher Learning Institutions (Makona, 2020).…”
mentioning
confidence: 99%
“…Complementing the findings reported by Steffens et al (2016, discussed above), in a longitudinal study of recent American retirees, Haslam, Lam, et al (2018) found that retiree identification (i.e., developing a strong sense of connectedness and belonging with retirees) and the development of new group memberships post‐retirement both mediated the relationship between multiple group memberships and improvement in retirement adjustment over a three month period. Relatedly, one of the major themes that emerged from a qualitative study of recently retired academics was the importance and centrality of academic identity (Miron et al, 2021). Here, the authors found that in preparation for retirement, academics needed to disidentify from this central identity.…”
Section: Introductionmentioning
confidence: 99%